“Land Fever” and “Bankruptcy”: Social Problems in Hanoi’s Urbanizing Peri-urban Communities - Nguyen Thi Thanh Binh, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Drawn upon field research in two peri-urban villages of Hanoi in 2014 and short re-visits recently, the research examines the widespread of gambling and other social issues in Hanoi’s urbanizing peri-urban communities which happened concurrently with the phenomenon of “land fever,” and at the time local villagers received compensation from land appropriation. The article aims to understand the impact of urbanization on these communities and the interface between urbanization and the increase of social problems. It argues that gambling, drug use, and other social problems have been existing in Vietnamese rural communities long before; however, when urbanization came, some people have higher chances to engage in these activities. Those are villagers who want to transform quickly into entrepreneurs or bosses by joining the “black credit” market and gambling. Together with middle-aged and old farmers who greatly relied on agricultural production and face difficulties in transforming their occupation, they formed the group of losers in the urbanization process.Received 6th January 2019; Revised 26th April 2019; Accepted 15th May 2019